2021
DOI: 10.6007/ijarbss/v11-i7/10397
|View full text |Cite
|
Sign up to set email alerts
|

Household Food Waste: Exploring the Modern Throw-away Culture in Raub, Pahang, Malaysia

Abstract: Food waste has formidable harmful consequences for food security, the environment, the economy, and biodiversity loss, making it a worldwide issue that demands immediate action. Reducing the amount of food waste has been deemed critical in Malaysia, thus, this study investigates the factors related to household food wastage with the aims of identifying the level of awareness as well as the causes and effects of food waste among residents of Raub, Pahang. It presents a qualitative research approach to allow the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This study adopted quantitative research because it allows for the easy collection of numerical data that can be utilized to assess and analyze the relationship between the two variables (McLeod, 2019). The population was narrowed down to Muslim in Klang Valley because, Klang Valley has the highest population density ("Department of Statistic Malaysia", 2022) and reported as the biggest contributor to unclaimed wealth amounted to 86% (Ahmad et al, 2019). The convenient sampling design was applied to provide the convenience of having any accessible sample as the subject under investigation (Sekaran & Bougie, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study adopted quantitative research because it allows for the easy collection of numerical data that can be utilized to assess and analyze the relationship between the two variables (McLeod, 2019). The population was narrowed down to Muslim in Klang Valley because, Klang Valley has the highest population density ("Department of Statistic Malaysia", 2022) and reported as the biggest contributor to unclaimed wealth amounted to 86% (Ahmad et al, 2019). The convenient sampling design was applied to provide the convenience of having any accessible sample as the subject under investigation (Sekaran & Bougie, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The study by Maamor et al (2020) found income and knowledge to be significant towards predicting Muslims' behaviour to choose Hibah. Ahmad (2019) discovers that attitude and promotion have significant effect on hibah awareness while Said et al (2020) employed Theory of Planned Behaviour (TPB) to identify intent for hibah among Muslims in Malaysia and found attitude, perceived behavioral control and subjective norms to have significant positive relationship with hibah intent. That study however only sampled a small percentage of the population and warrant further investigation to contribute more toward the hibah literature in Malaysia.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation